Understanding fibroblast-immune cell interactions via co-culture models and their role in asthma pathogenesis - Thiam, F.; Yazeedi, S. Al; Feng, K.; Phogat, S.; Demirsoy, E.; Brussow, J.; Abokor, F. A.; Osei, E. T. (Frontiers in Immunology, 2023)
Asthma is a chronic lung disease involving airway inflammation and fibrosis. Fibroblasts are the main effector cells important for lung tissue production which becomes abnormal in asthmatics and is one of the main contributors to airway fibrosis. Although fibroblasts were traditionally viewed solely as structural cells, they have been discovered to be highly active, and involved in lung inflammatory and fibrotic processes in asthma. In line with this, using 2D and 3D in vitro co-culture models , a complex interaction between lung fibroblasts and various immune cells important for the pathogenesis of asthma have been recently uncovered. Hence, in this review, we provide the first-ever summary of various studies that used 2D and 3D in vitro co-culture models to assess the nature of aberrant immune cell-fibroblast interactions and their contributions to chronic inflammation and fibrotic mechanisms in asthma pathogenesis